Flexicure labour market structures : the gretchenfrage of their added value - Hiessl, Christina (Array, 2019)
The article discusses the added value of social policy approaches which can be characterized as ‘flexicure’ based on a comparison of Germany and Austria. It offers an insight into some of the central labour market and policy developments in these countries, which share a number of common principles and structures but differ quite strikingly when viewed through the lenses of the flexicurity concept. This comparison serves as a basis for a discussion about the desirability of reforms to reinforce the ‘flexicurity score’ of any national legal order as well as the multitude of forms which the concept can take to match diverse legal and socio-economic traditions.